DOI: 10.31274/etd-180810-3773
|View full text |Cite
|
Sign up to set email alerts
|

Defining the energy and nutrient content of corn grown in drought-stressed conditions and determining the relationship between energy content of corn and the response of growing pigs to xylanase supplementation

Abstract: Recommended Citation Newman, Monica A., "Defining the energy and nutrient content of corn grown in drought-stressed conditions and determining the relationship between energy content of corn and the response of growing pigs to xylanase supplementation" (2014). Graduate Theses and Dissertations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
1

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 74 publications
(94 reference statements)
3
5
0
1
Order By: Relevance
“…Some studied like Jahanzad et al (2013) reported that drought condition may cause reduction in NDF and ADF concentration while it can improve the concentration of CP, DMD, WSC and DMD in forage sorghum cultivars. Similar type of findings was reported by Newman (2014) under drought stress conditions. Further, Xu &Lascano (2007) reported that drought stress reduced the silo quality.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Some studied like Jahanzad et al (2013) reported that drought condition may cause reduction in NDF and ADF concentration while it can improve the concentration of CP, DMD, WSC and DMD in forage sorghum cultivars. Similar type of findings was reported by Newman (2014) under drought stress conditions. Further, Xu &Lascano (2007) reported that drought stress reduced the silo quality.…”
Section: Introductionsupporting
confidence: 79%
“…Both ADF and NDF follow an incremental trend as interval irrigation increased (Table 3). Newman (2014) reported an association between the improvement of corn plant ADF and NDF content and drought stress. Similarly, Xu & Lascano (2007) reported that drought stress increased concentrations of both NDF and ADF forage by reducing the share of grain and ear in corn.…”
Section: Acid Detergent Fiber and Neutral Detergent Fibermentioning
confidence: 99%
“…The majority of initial research with exogenous xylanases in swine diets was done with wheat-based diets due to wheat being the primary cereal grain in Europe, where the xylanase enzyme was originally developed (Newman, 2014). Arabinose and xylose sugars from arabinoxylans make up approximately 62% of the NSP component in wheat, with the majority of these sugars being insoluble (Jaworski et al, 2015).…”
Section: Xylanase Enzymes In Swine Dietsmentioning
confidence: 99%
“…Results from previous research with exogenous xylanase supplementation in corn and corn by-products based diets have also been inconsistent. Xylanase supplementation in cornbased diets has shown benefits in some studies, including increased ATTD of DM (Newman, 2014;Passos et al, 2015), GE (Newman, 2014;Passos et al, 2015), and NDF (Fang et al, 2007;Passos et al, 2015), as well as improvements in ADG (Fang et al, 2007;Myers and Patience, 2014) and improved feed conversion ratio (Fang et al, 2007;Jones et al, 2015). In diets containing corn-DDGS, xylanase has been shown to increase the AID of GE, DM, CP, NDF, and ADF (Kiarie et al, 2016a), and has been shown to increase ADG, although the response was not consistent through the duration of the trial (Yang et al, 2016).…”
Section: Xylanase Enzymes In Swine Dietsmentioning
confidence: 99%
See 1 more Smart Citation